Self-Regulation in the Written Composition Processes in First-Year College Students of the Major of Veterinay Assistance at Universidad Técnica Nacional, Atenas Campus - Castro Campos, María Lourdes (2013)
First-year college students require an educational environment that will provide the foundation for their integral development. For this reason, classrooms should foster an environment of free communication and full development. These students are considered inexperienced or novice writers because they do not plan, do not set goals, do not take into account the audience, and do not have enough knowledge about strategies for essay writing in general. Thus, it would be ideal that in college, writers maximize their potential and transform not only their writing pattern but their knowledge in general starting from reflection and the discursive quality that they employ. All this can be accomplished with some self-regulation that would allow them to take over their text and make their writing autonomous since it originates from their particular perspective and according to their personal conceptions and socio-emotional ideology.